2017
DOI: 10.1002/aoc.3924
|View full text |Cite
|
Sign up to set email alerts
|

Equisetum arvense As an abundant source of silica nanoparticles. SiO2/H3PW12O40 nanohybrid material as an efficient and environmental benign catalyst in the synthesis of 2‐amino‐4H‐chromenes under solvent‐free conditions

Abstract: Uniform SiO 2 nanoparticles were successfully prepared from Equisetum arvense obtained from the north-east of Iran. Then, surface modification of the extracted nanoparticles was performed with a methanol solution of H 3 PW 12 O 40 via wet impregnation method. The prepared nanocatalyst was characterized by XRD, FESEM, ICP, UV-Vis, and FT-IR spectroscopy. The supported heterogeneous nanocatalyst was successfully applied as a Lewis/Bronsted acid catalyst in the synthesis of a series of substituted 4H-chromenes vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In connection with our ongoing work on the synthesis of various heterocyclic compounds [22][23][24][25][26][27][28][29], we wish to report a facile procedure for preparation of imidazole derivatives without addition of any specific catalyst. As mentioned above, several methods are introduced for the synthesis of trisubstitutedimidazoles and their derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…In connection with our ongoing work on the synthesis of various heterocyclic compounds [22][23][24][25][26][27][28][29], we wish to report a facile procedure for preparation of imidazole derivatives without addition of any specific catalyst. As mentioned above, several methods are introduced for the synthesis of trisubstitutedimidazoles and their derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…To reveal the advantages of this catalyst, its catalytic activity in the model reaction involving benzaldehyde, malononitrile and 4‐hydroxycoumarin was compared with those of previously reported systems (Table ). As evident from Table , the catalytic activity of Ag 3 PMo 12 O 40 was compared with other catalysts such as [DMAP‐PEG 1000 ‐DI L][BF 4 ], nano‐ZnO, crown ether complex cation ionic liquids (CECILs), ammonium acetate, titanium dioxide nanowires, nanomagnetic double‐charged diazoniabicyclo[2.2.2]octane dichloride silica hybrid (Fe 3 O 4 @SiO 2 /DABCO), surfactant‐modified bentonite (CTMAB‐bentonite), hexamethylenetetramine, SiO 2 /H 3 PW 12 O 40 nanohybrid, RuBr 2 (PPh 3 ) 4 , sodium malonate, NaCl, (NH 4 ) 42 [MoVI 72 MoV 60 O 372 (CH 3 COO) 30 (H 2 O) 72 ], a Keplerate‐type giant‐ball nanoporous isopolyoxomolybdate, silica‐supported molybdic acid, KNaC 4 H 4 O 6 ⋅4H 2 O (potassium sodium tartrate) and polypyrrole/Fe 3 O 4 /CNT that were previously used as catalysts in the same reaction. The results showed that compared to the other catalysts, our designed catalyst can catalyse the reaction in an appropriate manner.…”
Section: Resultsmentioning
confidence: 99%
“…Tandem reactions offer many opportunities to improve chemical transformations such as Lewis acid–base catalysis, hydrogenation reactions and alkene metathesis . MCRs are currently well‐established methods for the synthesis of heterocycles, natural products and polymers while Double and Triple Cascade Reactions are still a growing field of research. Knoevenagel condensation–Michael addition (Double Cascade Reactions) and Knoevenagel condensation–Michael addition–cyclization (Triple Cascade Reactions) Sequences have been widely studied and frequently applied to the synthesis of natural products and biologically active compounds .…”
Section: Introductionmentioning
confidence: 99%